Stimulus onset predictability modulates proactive action control in a Go/No-go task - Berchicci, Marika; Lucci, Giuliana; Spinelli, Donatella; Di Russo, Francesco (Frontiers in Behavioral Neuroscience, 2015)
The aim of the study was to evaluate whether the presence/absence of visual cues specifying the onset of an upcoming, action-related stimulus modulates pre-stimulus brain activity, associated with the proactive control of goal-directed actions. To this aim we asked 12 subjects to perform an equal probability Go/No-go task with four stimulus configurations in two conditions: 1) uncued, i.e., without any external information about the timing of stimulus onset; and 2) cued, i.e., with external visual cues providing precise information about the timing of stimulus onset. During task both behavioral performance and event-related potentials (ERPs) were recorded. Behavioral results showed faster response times in the cued than uncued condition, confirming existing literature. ERPs showed novel results in the proactive control stage, that started about 1 s before the motor response. We observed a slow rising prefrontal positive activity, more pronounced in the cued than the uncued condition. Further, also pre-stimulus activity of premotor areas was larger in cued than uncued condition. In the post-stimulus period, the P3 amplitude was enhanced when the time of stimulus onset was externally driven, confirming that external cueing enhances processing of stimulus evaluation and response monitoring. Our results suggest that different pre-stimulus processing come into play in the two conditions. We hypothesize that the large prefrontal and premotor activities recorded with external visual cues index the monitoring of the external stimuli in order to finely regulate the action.